A STANDARD STUDY OF INVESTIGATING THE IMPACT OF SOME ECONOMIC VARIABLES IN IRAQI INVESTMENT - Waleed Ahmed Hassen (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Before proceeding to study the fluctuations of any economic phenomenon, it is necessary to first ascertain the existence of a trend in the time series, and according to the nature of the growth of the series, we can distinguish between stable time series and unstable time series. The stable time series can be defined as that series whose levels change with time without changing the average in it during a relatively long period of time, meaning that the series has no tendency towards increase or decrease. As for the unstable time series, the average level in it is constantly changing, whether towards increase or decrease. The aim of this research is to show the extent of the impact of some economic variables represented by money supply, gross domestic product, national income, after reaching the state of stability for these variables, and it was concluded that most of these variables are unstable in the time series, but stable in the first difference. It was also concluded that the contribution of the independent variable (money supply) to investment is negative, and that the negative sign of the independent variable parameter (money supply) is consistent with the economic logic of the modern quantity theory (Chicago School) Friedman and his supporters that the growth of money supply should be proportional to the growth of money supply. Gross domestic product so as not to cause imbalances in the economy and thus its negative impact on investment. The growth of money supply in Iraq was not commensurate with the growth of the gross domestic product, because an increase in the money supply can affect some other economic factors, and some of these factors have an impact on the economy, leading to an increase in interest rates and consequently to a reduction in investment. The price level and the expected effect of inflation.